Physiological and health quality of peanut seeds during the production process - Barbosa, Rafael Marani; Vieira, Bruno Guilherme Torres Licursi; Martins, Cibele Chalita; Vieira, Roberval Daiton (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to evaluate the effect of production process stages on the physiological and health quality of peanut seeds. A completely randomized design with 12 treatments and four replicates was used. Treatments consisted of plant uprooting, plant gathering, transportation, drying, storage (two, four, and six months), and the following processing steps: mechanical threshing, classification by size, separation by density and color, and chemical treatment. Water content, health quality, germination, and vigor of seeds were evaluated after each treatment. Aspergillus spp. and Penicillium sp. were found in the seeds. In the first year, after mechanical threshing, seeds showed a reduced performance. In the production process, storage promoted the infection of 100% of the seeds by Aspergillus spp. The chemical treatment was effective in restoring seed health quality. Mechanical threshing steps and storage reduce the seed quality of peanut.